Scientific publications of doctors of science in nursing: Case report of a private university in Lambayeque, Peru - Díaz-Manchay, Rosa (2020)
The "sine qua non" work of research Universities is the generation of knowledge. This mission is a privileged task of the university community, formed mainly by professors with a doctoral degree. They develop the lines of research that their social environment demands. In Peru, according to the data from National Council of Science and Technology in 2015 only 39% and 40% of the total researchers working in public and private universities, respectively, have a doctoral degree, and 27% of the total belongs to the area of science and technology, while the health sector only reaches 15.9%. This group has made the guidelines and criteria for the categorization of a qualified researcher in our country, establishing for university teachers with a doctoral degree a moral imperative to achieve such a name based on the contribution shown in their line of professional performance. They are generating a personal level of public recognition as academic authorities, opinion leaders, and consultants thematic; as well as for the university, at the institutional level, the achievement of the processes of licensing and accreditation.